Strategi Noise: Eksplorasi Netnografi Konten Noise Di Akun Tiktok UMKM Indonesia - Wafi Muhammad; Meliaty Finthariasari (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2026)
Background: The rising number of TikTok users in Indonesia intensifies competition for audience engagement. Consequently, MSMEs innovate by employing chaotic and disruptive content presented in a humorous and ludicrous manner, referred to as noise. Aim: The purpose of this study is to examine how Indonesian MSMEs create and narrate noise content on TikTok, how audiences react to this content in the context of local digital culture, and to determine the prerequisites for success, efficacy constraints, and dangers of employing noise as a marketing communication strategy for MSMEs in the face of attention economy competition. Methodology: a retrospective netnography of postings from five Indonesian MSME TikTok accounts conducted between May and October. Data extraction via Apify.com encompassed 495 videos and 1,426 comments. A purposive sampling method with a maximum variation strategy was employed. Inductive thematic analysis was performed in five stages. Continuous engagement, triangulation, peer debriefing, and negative case analysis validate the findings. Results and Discussion: Five MSME accounts show a variety of noise characteristics, including cultural adaptation, aggressive integration, raw editing, memes, and AI-generated content, according to the research findings. Positive resonance, which is typified by a sense of in-group belonging and shared humor, and interrogative replies, which comprise inquiries expressing interest and a need for more information, are the two primary types of audience responses. The congruence of brand identity, audience expectations, and message delivery all affect how effective noise strategy is. While @geroz_official only reached 1.74% because of the predominance of repetitive hard selling and little story innovation, the @danielbudianto28 account obtained the greatest engagement rate of 8.25% because of a soft selling strategy and contextual content diversity. Conclusion: The noise strategy represents a daring and inventive approach to engaging viewers in a congested media landscape. The five MSMEs recognized that incorporating noise would yield distinction along with cost reductions. Implications for Research: The noise strategy can be regarded as a strategic and sustainable innovation that facilitates algorithmic negotiation among creators, viewers, and platforms. The Noisy Marketing Implementation Framework was developed for SMEs to encompass tools for evaluating preparation, content guidelines, risk mitigation checklists, and performance indicators. Limitations: This analysis pertains to five micro, small, and medium-sized firms (MSMEs) within the F&B and service sectors, encompasses a six-month observation period, concentrates on public comments, lacks long-term data regarding brand loyalty, and is restricted to a single platform.